Ritual Kematian dalam Masyarakat Suku Alas di Desa Batu Mbulan II, Aceh Tenggara - Ainun Mardiah; Sori Monang; Aulia Kamal (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan Pusat Jurnal Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The Alas people in Batu Mbulan II Village, Southeast Aceh have a unique tradition related to death. This ritual has been practiced across generations and still exists today because it is believed to have a function in their lives. This study wants to know how the death ritual is practiced by the Orang Alas in Batu Mbulan II Village; what does it mean; and its function in their social life. This is a qualitative research using case studies where data is collected through interviews and observations. The data were analyzed descriptively, and showed that: 1) The death ritual practiced by the Orang Alas in Batu Mbulan II Village is part of the local interpretation of tajhiz mayit in Islam. The ritual begins with bathing the corpse in the river, mengkiran (surrounding the coffin), talkin (teaching the dead), samadiyah (sending reward, praying for the dead, blessing tombstones and white stones). 2) This ritual has a number of meanings, as a way of remembering the dead, helping him, honoring his family; and 3) having social functions such as, strengthening solidarity, cooperation. This study shows that rituals are not only oriented to spiritual and mystical matters, but also social life